IN-SILICO DESIGN, SYNTHESIS, ANTI-INFLAMMATORY AND ANTICANCER EVALUATION OF PYRAZOLINE ANALOGUES OF VANILLIN (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A series of novel pyrazoline derivatives of vanillin were synthesized. The hydroxyl group in vanillin was masked by converting into methyl vanillin. The methyl vanillin was allowed to condense with different acetophenone derivatives gave chalcone derivatives and finally cyclized with thiosemicarbazide to form the pyrazoline derivatives of vanillin. Docking studies were carried out against anti-inflammatory cyclooxygenase receptor and anticancer farnesyl transferase receptor. Majority of the synthesized compounds showed good fitting with the active site of all the docked targets. The synthesized compounds had shown significant anti inflammatory and anticancer activities.